A Naphtho‐Fused Double [7]Helicene from a Maleate‐Bridged Chrysene Trimer. Issue 12 (9th February 2017) - Ferreira, Marli; Naulet, Guillaume; Gallardo, Hugo; Dechambenoit, Pierre; Bock, Harald; Durola, Fabien
Abstract: Perkin condensation of chrysenyl‐6‐acetic acid with chrysenylene‐6, 12‐diglyoxylic acid followed by in situ esterification gives a bismaleate, whose conjugated stilbene moieties are efficiently shielded against intermolecular condensations and undergo iodine‐catalyzed oxidative photocyclization in toluene without the need for high dilution. The concentration is limited by the low solubility of the flexible bismaleate at room temperature. The so‐obtained double [7]helicene crystallizes in a nonchiral meso form. It is notably more soluble than its flexible precursor because it cannot fold to optimize π–π stacking. Abstract : It takes only five consecutive steps from unsubstituted chrysene to obtain an all‐ kata ‐annulated arene tetracarboxylate, in which two heptahelicene segments are joined together. The bishelicene is formed in the achiral meso configuration, with the two helices having opposite pitches.